Nostalgia Pop: Analysis of the Representation of Francoism on TikTok - Martínez Antón, Pablo; Cano-Orón, Lorena (Historia y Comunicación Social, 2026)
TikTok is one of the most widely used social media platforms among young people in Spain and plays a key role in their news consumption. In a European context marked by the rise of the far right—characterized by discourses sympathetic to dictatorial pasts and the presence of disinformation in its activism—it is pertinent to analyze the imaginaries constructed on this platform regarding nostalgia for Spain’s dictatorial past. This study examines a total of 283 history-related videos, obtained through a scraping process of search results associated with keywords related to Francoism. A content analysis was conducted on this corpus based on eight variables focused on authorship, thematic content, nostalgia, and affective practices, alongside a discourse analysis. The results show that the majority of the analyzed users are anonymous and that their content evokes Francoism through a form of restorative nostalgia.
Keywords: Political Nostalgia; Populism; Social Media; Democratic memory; Political communication